Critical Language Study and Translation: The Case of Academic Discourse - Bennett, Karen (2012)
This chapter uses Critical Discourse Analysis to show the very different ideologies encoded into Portuguese and English academic discourse,arguing that translation from one to the other is virtually impossible within the genre of the academic article.